Assessment of NK cell-mediated cytotoxicity by flow cytometry after rapid, high-yield isolation from peripheral blood - Holicek, Peter; Truxova, Iva; Kasikova, Lenka; Vosahlikova, Sarka; Salek, Cyril; Rakova, Jana; Holubova, Monika; Lysak, Daniel; Cremer, Isabelle; Spisek, Radek; Fucikova, Jitka (Methods in enzymology, 2020)
Natural killer (NK) cells constitute the predominant innate lymphocyte subset that mediates the anti-viral and anti-tumor immune responses. NK cells use an array of innate receptors to sense their environment and to respond to infections, cellular stress and transformation. The resulting NK cell activation, including cytotoxicity and cytokine production, is a fundamental component of the early immune response. The most recent discoveries in NK cell biology have stimulated the translational research that has led to remarkable results for the treatment of human malignancies. Therefore, the rapid isolation of NK cells from the peripheral blood or tumor microenvironment and the subsequent assessment of cytolytic function are crucial to the study of their potency and NK cell-mediated immunosurveillance. Here, we provide protocols for NK cell isolation and the assessment of NK cell cytotoxicity using flow cytometry.
Keywords: Cytotoxicity, Immunologic; Cell Separation; buňky NK; Lymphocyte Activation; aktivace lymfocytů; separace buněk; lidé; cytotoxické testy imunologické; cytotoxicita imunologická; Flow Cytometry; Killer Cells, Natural; Cytotoxicity Tests, Immunologic; průtoková cytometrie; Humans